An analysis of the HR management system in BPO company in Bangladesh focusing on Quantanite BD - Tanvi, Sakib Hossain (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.